LD50 and affective dose of Eruca sativa mill (gergeer) ethanolic extract - Rana Abdulla Salih; Zuhair Abdulkareem. Dawah (University of Thi-Qar Journal of agricultural research, 2022)
Cardiotoxicity is defined as drug-induced damage to the heart muscle, which can result in cardiac failure or cardiac arrest. Cardiotoxicity is a common side effect of traditional anticancer drugs such as doxorubicin, taxanes, 5-fluorouracil, and cyclophosphamide, as well as newer agents such as biological antibodies such as Nivo. Cardiotoxicity is also caused by the long-term use of neurologic/psychiatric medications. This study was designed to determine the effect of eruca sativa mill (Gergeer) leaves extract on cardiotoxicity induced by doxorubicin in rabbits. The fifty-four rabbits used in this study were obtained from a local rabbit breeder. Animals ranged between 1-1.3 years old, and their weight was approximately 1-2kg without specifying gender experiment Acute toxicity study, The pilot study to determine the LD50 dose of Eruca sativa mill (gergeer) by "up and down" method after acute exposure in rabbits, The effective dose of Eruca sativa mill (gergeer) was determined by using a simple line equation. The effective dose of Eruca sativa. troponin I determine the level of proteins in the blood increase in heart attack,.The Troponin-I level of the control positive group revealed a significant increase as compared with G3, G4, G5, and the control negative group.The cTn-I level of the G3 significant increase is compared with treated G4,G5 group and control negative group with a significant decrease is compared with G1, G2 group and control positive group ; while treated G4 ,G5 group significant decrease is compared with treated G1,G2,G3 group and control positive, Log number dose-response curve and maximum effective dose the simple line equation revealed that the effective Eruca sativa dose of Troponin I level was (3.01 , 2.99 ,1.97 ,1.015, 1.030) (ng/ml) respectively, whereas the effective Eruca sativa dose of Troponin I was 316 mg/kg. conclusion , The effective dose-response results asymptotic to 10 % of LD50, induced cardiac toxicity with DOX appear biochemically, cardiographycally and histopathologically, The Eruca sativa mill (gergeer) extract was effective protective for induced cardiac toxicity.